Comparative analysis of government policies in small claims cases In Indonesia, Malaysia and the Philippines - Feliprada, Glenda E. (2018)
The Small Claims Courts in Indonesia, Malaysia and the Philippines are established to increase access to justice by the marginalized and disadvantaged individuals who have no financial capacity to secure legal assistance and protection. These courts are supposed to protect the rights of the plaintiff and increase their access to justice through low cost and fast litigation of cases. However, there are corporations who tend to manipulate the legal mechanisms in their favour and against the plaintiffs. This situation gave impetus to this study and raised the question on how the Small Claims policies in the three countries protect the rights of the plaintiffs and increase their access to justice. Specifically, this study aims to: 1) compare and contrast the government policies and mechanisms implemented by the Small Claims Court in the three countries; 2) elicit the perspectives of the implementers and the litigants in terms of the relevance, feasibility and outcome of the Small Claims Courts; 3) assess the legal effectiveness of the Small Claims Courts given the existing resources, manpower and other limitations; and 4) determine the efficiency and effectiveness of resolving Small Claims Cases in upholding the rights of the marginalized and disadvantaged. The qualitative method of research was used in this study. The primary data were gathered through in-depth interview, and the secondary data were obtained from the court dockets and court resolutions of the Judicial Branch of Indonesia, Malaysia and the Philippines. The participants of this study were 10 court implementers and 10 litigants as plaintiff and defendants in Small Claims Courts from each of the three countries. They were chosen through purposive sampling. Thematic analysis was used to analyze the primary data gathered through the interviews conducted, and frequency counts, percentage and mean were used to analyze the secondary data obtained from the Judicial Branch of the three countries. The findings of the study revealed that Malaysia and the Philippines implemented egalitarian theory and litigations were conducted without lawyers. The litigations secured procedural, substantive justice and reciprocity in court resolutions in serving equity between parties. However, Indonesia has to refine Small Claims policy to achieve equity. In the Philippines and Indonesia, the Small Claims Courts are perceived by the public with diverse political behaviour in favour of the corporate creditors instead of individual debtors, while Malaysia’s Small Claims Procedure disqualifies corporations as plaintiffs. The three countries failed to address public awareness for the full empowerment of the marginalized in the society through the government policy on Small Claims Cases. The Small Claims Courts in the Philippines and Malaysia were efficient and effective in the enforcement of payment in compromise agreement with twelve (12) percent legal interest rate per annum and decision on merits with zero interest rates respectively. However, Indonesia failed to achieve the goal of Small Claims Court. Corporations, without restriction of cases withdrawal in court, manipulated extra-judicial settlement in their favour against the plaintiff at the minimum interest rate of two point five (2.5) percent per month.